2006
DOI: 10.1196/annals.1317.064
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pituitary Adenylate Cyclase‐Activating Polypeptide, Vasoactive Intestinal Polypeptide, and Somatostatin on the Release of Thyrotropin from the Bullfrog Pituitary

Abstract: The recent development of a specific radioimmunoassay for amphibian (bullfrog, Rana catesbeiana) thyrotropin (TSH) has made it possible to study the effects of various neuropeptides on the release of TSH from the pituitary in vitro. Up to now, corticotropin-releasing factor of bullfrog origin has been shown to have a potent TSH-releasing activity, whereas gonadotropin-releasing hormone and TSH-releasing hormone exhibit a moderate TSH-releasing effect on the adult, but not larval, pituitary. In the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…Among several postulated roles, pacap is known as a releasing factor for hormones, including adenohypophysial hormones (Rawlings and Hezareh, 1996). pacap was shown to increase the secretion of Growth Hormone (Gracia-Navarro et al, 2002; Wong et al, 2000; Zhou et al, 2005), Gonadotropin (Petersen et al, 1996; Wong et al, 2000), Thyrotropin (TSH; (Okada et al, 2006), and Prolactin (Rawlings and Hezareh, 1996). …”
Section: Resultsmentioning
confidence: 99%
“…Among several postulated roles, pacap is known as a releasing factor for hormones, including adenohypophysial hormones (Rawlings and Hezareh, 1996). pacap was shown to increase the secretion of Growth Hormone (Gracia-Navarro et al, 2002; Wong et al, 2000; Zhou et al, 2005), Gonadotropin (Petersen et al, 1996; Wong et al, 2000), Thyrotropin (TSH; (Okada et al, 2006), and Prolactin (Rawlings and Hezareh, 1996). …”
Section: Resultsmentioning
confidence: 99%
“…More recently, use of receptor‐specific somatostatin analogs on clinically nonfunctioning pituitary adenoma cells cultured in vitro indicated that the regulation of alpha‐subunit secretion by SST is mediated through the subtypes sst2A, sst3, and sst5 50 . SST has also been reported to inhibit stimulated TSH release in vitro from fetal human pituitary cells, as well as in cultures of pituitary cells from rats, birds, and amphibians 27,29,51,52 . In fact, in this latter species, it has been demonstrated that both SS1 and SS2 inhibited TSH release induced by PACAP‐38 but did not alter spontaneous (basal) TSH secretion, suggesting a similar role for both neurohormones in the regulation of thyrotrope function in vitro 27 .…”
Section: Sst Functions From Fish To Mammalsmentioning
confidence: 95%
“…By and large, SST acts as a universal inhibitor of endocrine and exocrine secretions. Thus, SST inhibits GH secretion in all vertebrate species studied, 7–18 while its actions in other pituitary secretions vary in a species‐dependent manner 19–30 . In addition, SST14 inhibits exocrine secretions 4,5,31 and modulates nervous system functions and digestive and immune system actions 32,33 .…”
Section: Introductionmentioning
confidence: 99%
“…Although they have mainly been studied in mammals, some of these actions have also been reported in other vertebrates (for a review, see Gahete et al (2010)). For instance, SS1 inhibits prolactin release in the Mozambique tilapia (Oreochromis mossambicus; Grau et al 1982) and PACAP38-induced TSH secretion in the American bullfrog (Lithobates catesbeiana, previously Rana catesbeiana) (Okada et al 2006). Surprisingly, in the trout (Salmo trutta), SS1 seems to exert a stimulatory effect on ACTH secretion (Langhorne 1986).…”
Section: Ss-ergic Systemsmentioning
confidence: 99%
“…The idea that the genomes of vertebrates are the result of two rounds of genome duplications was first suggested by Ohno (1970) based on chromosome numbers and genome sizes. Information about gene locations on chromosomes in human and mouse genomes provided evidence supporting this notion in the late 1980s and early 1990s (Lundin 1993).…”
Section: Introductionmentioning
confidence: 99%